Development of generator aggregation technique for power system [electronic resource] - Ali Asghar Shojaei, 1979- (Skudai : Universiti Teknologi Malaysia, 2009)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2009